Elephant House - Blau, Dick, 1943- (Book collections on Project MUSE., 2015)
"Traces the history of the Asian elephant display at the Oregon Zoo from the 1950s to the present. An introduction by historian Nigel Rothfels explores changes in elephant husbandry since the 1870s"--